2021
DOI: 10.3390/biomedicines9111662
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs and lncRNAs: Potential Non-Invasive Biomarkers for Endometriosis

Abstract: Many studies have tried to understand the mechanism of endometriosis and its manner of manifestation. However, the only method of diagnosis considered as the gold standard in endometriosis is an invasive method called exploratory laparoscopy. Hence, there is a need to identify non-invasive or minimally invasive methods to minimize patients’ suffering, thus increasing their addressability at the earliest possible staging of the disease, and to diagnose this condition as soon as possible. miRNAs (microRNAs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…miRNAs have entered the horizon as potential diagnostic markers for diseases, and circulating miRNAs in plasma and serum are recommended as non-invasive biomarkers for EMs. Many miRNAs have been found to be differentially expressed between EMs and healthy tissues, including miR-138, miR-199-5p, miR-20a, miR-34c, and miR-449 (Bjorkman and Taylor, 2019;Vanhie et al, 2019;Maier and Maier, 2021), which is consistent with our prediction and confirms the reliability of our study. Additionally, our study identified several miRNAs, whose association with EMs has not been previously reported in relevant studies.…”
Section: Discussionsupporting
confidence: 92%
“…miRNAs have entered the horizon as potential diagnostic markers for diseases, and circulating miRNAs in plasma and serum are recommended as non-invasive biomarkers for EMs. Many miRNAs have been found to be differentially expressed between EMs and healthy tissues, including miR-138, miR-199-5p, miR-20a, miR-34c, and miR-449 (Bjorkman and Taylor, 2019;Vanhie et al, 2019;Maier and Maier, 2021), which is consistent with our prediction and confirms the reliability of our study. Additionally, our study identified several miRNAs, whose association with EMs has not been previously reported in relevant studies.…”
Section: Discussionsupporting
confidence: 92%
“…It is well documented that miRNA expression in the human endometrium is dependent on the menstrual cycle phase and is regulated by sex steroids [ 106 ]. A broad range of different miRNAs involved in the pathogenesis of endometriosis and ectopic pregnancy has been described and they are summarized in Figure 3 [ 35 , 106 , 107 , 108 ]. In this part of the review, we focus on miRNAs that may constitute a link between these two diseases.…”
Section: The Role Of Micrornamentioning
confidence: 99%
“…In comparison to healthy controls, most lncRNAs are found in patients with malignant tumors [ 25 , 49 ]. Due to high expression levels of lncRNAs in tumors, lncRNAs can be found in body fluids such as blood, saliva, and plasma, suggesting that circulating lncRNAs may be employed as non-invasive tools for diagnosis of various cancers, including HCC [ 25 , 49 , 131 , 132 ].…”
Section: Cancer-associated Lncrnasmentioning
confidence: 99%